Studi Fatwa Nahdlatul Ulama (NU) No. 005/MNU-33/VIII/2015 Tentang Hukum Alih Fungsi Lahan Perspektif Maslahah - Sulhani Hermawan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
This paper highlights that Nahdlatul Ulama (NU), Indonesia’s largest Muslim organizations,contributes its basic principles to food sovereigntyover the country. One of the national contributions is demonstrated throughthe fatwa No. 005/MNU-33/VIII/2015 in Bahtsul Masa’il ad-Diniyyah al-Waqi’iyyah point VII on Land Use Conversion Lawissued when holding the 33rd NU national congress (muktamar) in Jombang, East Java.The fatwa issuance denotes an alternative to enhance Indonesia’s food sovereignty. This present study aims to investigate the Islamic edict concerning land use conversion law in the perspective of maslahah (public interests/benefits). A qualitative approach was employed in this library research. The fatwa No. 005/MNU- 33/VIII/2015 in Bahtsul Masa’il ad-Diniyyah al-Waqi’iyyah point VII on Land Use Conversion Law was used as the primary data. The study applies the theory of maslahah to analyze the data. The finding promotes that the law argument over the haram aspect of the land use conversion in the fatwa indicates the existence of maslahah and the prevention of darar (harm conditions) due to the land conversion.